Atypical phenotypes associated with pathogenic CHD7 variants and a proposal for broadening CHARGE syndrome clinical diagnostic criteria. Issue 2 (21st November 2015) - Hale, Caitlin L.; Niederriter, Adrienne N.; Green, Glenn E.; Martin, Donna M.
Abstract : CHARGE syndrome (Coloboma of the eye, Heart defects, Atresia of the choanae, Retardation of growth and/or development, Genital and/or urinary anomalies, and Ear malformations, including deafness and vestibular disorders) is a genetic condition characterized by a specific and recognizable pattern of features. Heterozygous pathogenic variants in the chromodomain helicase DNA‐binding protein 7 ( CHD7 ) are the major cause of CHARGE syndrome, and have been identified in 70–90% of individuals fulfilling clinical diagnostic criteria. Since 2004, when CHD7 was discovered as the causative gene for CHARGE syndrome, the phenotypic spectrum associated with pathogenic CHD7 variants has expanded. Predicted pathogenic CHD7 variants have been identified in individuals with isolated features of CHARGE including autism and hypogonadotropic hypogonadism. Here, we present genotype and phenotype data from a cohort of 28 patients who were considered for a diagnosis of CHARGE syndrome, including one patient with atypical presentations and a pathogenic CHD7 variant. We also summarize published literature on pathogenic CHD7 variant positive individuals who have atypical clinical presentations. Lastly, we propose a revision to current clinical diagnostic criteria, including broadening of the major features associated with CHARGE syndrome and addition of pathogenic CHD7 variant status as a major criterion. © 2015 Wiley Periodicals, Inc.